Local forest structure, climate and human disturbance determine regional distribution of boreal bird species richness in Alberta, Canada - Zhang, Jian; Kissling, W. Daniel; He, Fangliang (Journal of biogeography, 2013)
Aim: It is challenging to disentangle how local habitat structure, climate, and human disturbance interplay to determine broad-scale variation of species richness. Here, we separated various measures of local forest structure and composition, abiotic factors, and human land cover that constrain species richness of bird guilds in the boreal forest. Location: Boreal forest, western Canada. Methods: Data on breeding birds, habitat structure, climate and human foot-prints in 206 sites were sampled, with each site centred on an area of 1 ha in size. The 206 sites cover a large geographical extent with a distance of c. 1000 km between the most distant sites. We modelled bird guild species richness in relation to forest structure and composition (woody plant richness, forest biomass, number of vegetation layers, canopy openness), abiotic environment (temperature, precipitation, elevation), and percentage area of human land cover. We classified bird species into different guilds based on dietary preference, habitat specialization and migratory status, and used structural equations to quantify effect strengths of predictor variables. Results: We found that temperature, low levels of human land cover, woody plant richness and number of vegetation layers had strong positive correlations with overall bird species richness in the boreal forest. Moreover, local forest structure and composition showed a pronounced variation in their relationships with species richness of different guilds. Insectivores, old-growth forest specialists, forest generalists, long-distance migrants and winter residents showed strong positive correlations with woody plant richness, whereas old-growth forest specialists and winter residents were strongly related to forest biomass as well. The number of vegetation layers was positively related to species richness of most guilds, whereas the response to canopy openness was most pronounced for old-growth forest specialists and winter residents (being negatively correlated). Main conclusions: In addition to climate and human disturbance, local forest structure and composition are important determinants of broad-scale variation of bird species richness in boreal forest. However, the strength and direction (positive/negative) of determinants is guild-specific, suggesting a strong functional component to community structure.